Hubungan Pembelajaran Daring di Era Pandemi Covid 19 Terhadap Keaktifan Warga Belajar Program Kesetaraan Paket C di Pusat Kegiatan Belajar Masyarakat (PKBM) Se-Kabupaten Malang Provinsi Jawa Timur - Firdaus, Fikri (Universitas Negeri Surabaya, 2023)
Online learning is a learning process that is carried out without face to face and can be anywhere using an internet connection, online learning uses various applications to support the learning process. The purpose of this research is to know the process of online learning, the activeness of learning citizens, and the relationship of online learning to the activities of learning citizens. The number of respondents in this study were 120 students. This type of research uses a quantitative approach. Data collection using a questionnaire. The results showed that: (a) the online learning process of the package C equivalence education program at the Community Learning Activity Center (PKBM) was in the very good category. (b) the activeness of citizens learning the package C equivalence education program in the very good category and (c) there is a relationship between online learning in the Covid 19 pandemic era and the activities of citizens studying the package C equivalence education program in PKBM throughout Malang Regency.